Navigating Moral Cleansing: the Role of the 'Macbeth Effect' in Decision-Making Among Leaders of Private Nursing Schools - Imelda Ingir Ladjar; Warjiman Warjiman; Maria Frani Ayu Andari Dias; Mohammad Basit (GLOBAL HEALTH SCIENCE GROUP, 2024)
Private nursing schools in South Kalimantan face increasing pressure to produce high-quality, ethically driven nursing professionals, aligning with Indonesia’s “Golden Vision 2045.” Within this context, the